PENGARUH KEJELASAN SASARAN ANGGARAN DAN SISTEM INFORMASI TERHADAP AKUNTABILITAS KINERJA INSTANSI DENGAN PENGENDALIAN AKUNTANSI SEBAGAI VARIABEL MODERASI (PENELITIAN PADA BADAN PENGELOLA ASET DAN KEUANGAN DAERAH (BPKAD) PROVINSI JAWA TIMUR) - Rahmasi, Jne Riske; Murni, Siti Asiah (JURNAL LENTERA AKUNTANSI, 2023)
Agencies, established by the government to handle its affairs, play a crucial role in the successful execution of the mission to achieve the aspirations of the Indonesian state. The accomplishments of government agencies can be gauged through information on the performance accountability of each respective government institution. This information is essential, as it serves as the basis for governmental decision-making in improving management practices for better governance. The objective of this research is to analyze the influence of budget clarity and reporting system on the performance accountability of government agencies, with accounting control as a moderating variable. The sample for this study comprises employees working in the Finance Department (Accountancy BPKAD) or related financial fields, totaling 57 respondents, and the data were processed using SPSS. Data collection involved primary data obtained through targeted sources via questionnaire distribution. The research findings indicate that accounting control moderates the clarity of budget goals and reporting systems concerning the performance accountability of BPKAD agencies. Keywords: Clarity Of Budget Goals, Reporting System, Agency Performance Accountability, Accounting Control